Key points on Bichler/Nitzan's text “Capital as Power” - Achim Szepanski (The Bichler & Nitzan Archives, 2024)
FROM THE ARTICLE: At first glance, it would appear that Deleuze's concept of structure involves a complex form of so-called creorder, a term that appears at the forefront of the methodological findings of the economists Bichler/Nitzan. If the structure is actualized in each of its moments in processes, then Bichler/Nitzan describe this process with the term “creorder”. They consider this to be a highly artificial term, which is intended to indicate that a structure/order must constantly construct and reconstruct itself in (historical) time, just as a form must constantly transform itself. According to Bichler/Nitzan, in the context of creorder, the meaning of the relationship between Heraclitean becoming and Parmenidean being lies precisely in the fact that the fusion of verb and noun results in the term “creorder”: “To have a history is to create order – a verb and a noun whose fusion yields the verb-noun creorder.” On the one hand, the so-called creorder may be completely vertically or hierarchically ordered, as is the case in ultra-bureaucratic systems, for example; on the other hand, it may also be horizontal, as could be the case in radical democracies, or it may be in between order and disorder.
Keywords: P00; P1; 330; capital accumulation; capital as power; creorder; capitalization; differential accumulation; dominant capital; finance; Marxism; neoclassical economics; quantification; value